2022
DOI: 10.1186/s44201-022-00012-7
|View full text |Cite
|
Sign up to set email alerts
|

Intervention during wait time: identification and referral of individuals non-adherent for colorectal cancer screening

Abstract: Background Despite unanimous recommendations from numerous specialty societies on regular colorectal cancer screening, a substantial proportion of eligible adults are non-adherent with screening. The current study investigated whether research associates (RAs) in the emergency department (ED) can adequately assess patients’ adherence with colorectal cancer screening recommendations, outlined by the US Preventive Services Task Force (USPSTF), and provide referrals to individuals who are found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
2
Order By: Relevance
“…Despite the fact that only 8.3% of participants reported that COVID-19 delayed their cancer screening, our findings found relatively high rates of patients overdue on screening compared to past studies conducted in the ED prior to the pandemic (overdue rates 12–33% for cervical, 9 11 12–46% for breast, 5 , 10 12 and 17–46% for CRC screening 5 , 12 , 13 ). Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Despite the fact that only 8.3% of participants reported that COVID-19 delayed their cancer screening, our findings found relatively high rates of patients overdue on screening compared to past studies conducted in the ED prior to the pandemic (overdue rates 12–33% for cervical, 9 11 12–46% for breast, 5 , 10 12 and 17–46% for CRC screening 5 , 12 , 13 ). Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population.…”
Section: Discussioncontrasting
confidence: 88%
“…Our higher rates of overdue screenings were probably due not to the pandemic but may have been related to the characteristics of our patient population. Our study had much higher percentages of Asian (7%) and Hispanic (30%) participants than other similar studies, which had 1–3% 5 , 9 , 10 , 13 and 7–18%, 5 , 10 13 , 25 respectively. Additionally, in our study Spanish-speaking patients represented 15% of all participants.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation